FEATURES OF THE ANATOMY OF SOME BONES OF THE FACIAL PART HEADS OF A BACTRIAN CAMEL - Dnekeshev, A. K.; Zhubantaev, I. N.; Kakishev, M. G. (Ғылым және білім=Наука и образование=Science and education № 4-1 (69)., 2022)
he nasal and incisor bones of the Bactrian camel are represented by paired bones, which are located in the front of the skull and have features in the anatomical structure, unlike other agriculturalanimals. In a camel, the nasal bones have the appearance of two flat bones, which participate in theformation of the roof of the nasal cavity and are divided into external and internal surfaces. Incomparison with cattle, the length of the nasal bone of a Bactrian camel due to the shape and locationof the nostrils on the dorsal part of the nose is half as much and not covers the entire nasal cavity, aswell as in dogs. The nasal part of the nasal bone in a camel is much expanded than in other animals,looks like a wing and forms two bends - internal and external. The lateral edge of the wing of the nasalbone is involved in the formation of the inner part of the lacrimal opening, which in the camel has adifferent size and shape. The incisive bones of the camel are topographically located in front of themaxillary bones and serve as a bone base for the nostrils, forming the entrance to the nasal cavity andform the anterior part of the bone palate and holes for the alveoli of the anterior canines, which arepresent in males and females. In our study, the camel was compared with a large cattle does not havean incisive-nasal suture and, accordingly, does not have a nasopharyngeal notch. An anatomical studyof the bones of the facial part of the skull of the Bactrian camel was carried out according to certain methods. the facial part of the animal's skull depending on the physiological loads of the respiratorysystem in different age periods.Носовые и резцовые кости у верблюда-бактриана представлены, парными костями,которые расположены в лицевой части черепа и имеют особенности в анатомическом строениив отличие от других сельскохозяйственных животных. У верблюда носовые кости имеют виддвух плоских костей, которые участвует в образовании крыши носовой полости и делятся нанаружные и внутренние поверхности. В сравнении с крупным рогатым скотом длина носовойкости верблюда-бактриана из-за особенности формы и расположение ноздрей на дорсальной части носа вдвое меньше и не прикрывает полностью носовую полость, так же как и у собак.Назальная часть носовой кости у верблюда сильно расширен, чем у других животных, имеетвид крыла и образует два изгиба – внутренний и наружный. Латеральный край крыла носовойкости участвует в образовании внутренней части слезного отверстия, которая у верблюда имеетразный размер и форму. Резцовые кости у верблюда топографически располагаются впередиверхнечелюстных костей и служат костной основой для ноздрей образуя вход в носовую полость и формируют переднею часть костного неба и луночки для альвеол передних клыков,которые имеются у самцов, и у самок. В нашем исследовании верблюд в сравнении с крупнымрогатым скотом не имеет резцовоносового шва и соответственно неимеет носорезцовойвырезки. Анатомическое изучение костей лицевой части черепа верблюда-бактрианапроводилась согласно определенным методикам. Результаты исследования по динамикескорости роста и развития носовой кости верблюда-бактриана в постнатальном персоответствуют изменениям линейных промеров анатомических образований и костей лицевойчасти черепа животного в зависимости от физиологических нагрузок дыхательной системы вразные возрастные периоды.
Keywords: научный журнал; ринц; отечественное издание; периодическое издание; журнал коксон; верблюдоводство; bactrian camel; comparative anatomy; skull morphology; craniometry; nasal bone; носовые кости верблюда; анатомия верблюда; анатомия черепа верблюда